Law and the Universities - Paul A. Freund (Washington University Law Quarterly, 1953)
My theme is not the contribution that general education can make to law. My theme is the less familiar one, the contribution that law can make to general education. Instead of concentrating on the content of pre-legal studies for lawyers, I suggest that some thought be given to the legal content of nonlegal studies. The universities are experimenting successfully with courses on science for the citizen, aimed at an appreciation of scientific method or the tactics and strategy of science; courses have been introduced on economics for the citizen (known affectionately in some places as “economics for the idiot”); and similarly, in the name of general education, studies have been encouraged in the history of the pervasive problems of political thought. Yet, so far as I am aware, almost no effort has been made to provide the general student with an introduction to an understanding of the legal order. The neglect is all the more striking when we remember that the institutions which are central to our civilization-security of the person, freedom of the mind, ownership, and the intercourse of trade-and which at the same time are the substance of our daily living, are all dependent on a structure of law. Should the student, whose preparation for mature living must include a study of Boyle’s law of gases, be left unexposed to Pound’s Spirit of the Common Law and Cardozo’s Nature of the Judicial Process?
Keywords: Legal education